2018
DOI: 10.1007/s00204-018-2209-9
|View full text |Cite
|
Sign up to set email alerts
|

Using the lentiviral vector system to stably express chicken P-gp and BCRP in MDCK cells for screening the substrates and studying the interplay of both transporters

Abstract: Transporters P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) are known to influence the pharmacokinetics and toxicity of substrate drugs. However, no detailed information is as yet available about functional activity and substrate spectra of chicken P-gp and BCRP. In this study, BCRP single and BCRP/P-gp double-transfected MDCK cell lines (named MDCK-chAbcg2 and MDCK-chAbcg2/Abcb1, respectively) were generated using lentiviral vector system to develop reliable systems for screening the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In order to elucidate the mechanism of TMS-NLCs enhancing the oral absorption of TMS, the effect of NLCs on the TMS permeability across Caco-2 cell monolayers was investigated. In our previous study, tilmicosin was proved to be a substrate of P-gp, a drug efflux transporter [35]. Herein, we found that the efflux rate of 10% TMS in Caco-2 cell monolayers was 2.29 (Table 2), far higher than the 1.5 regulated by the United States Food and Drug Administration [36], further demonstrating that TMS as the substrate of P-gp could be removed from intestinal epithelial cells and its oral absorption thereby decreased [25].…”
Section: Evaluation Of Tms Permeability Across Caco-2 Cell Monolayersmentioning
confidence: 99%
“…In order to elucidate the mechanism of TMS-NLCs enhancing the oral absorption of TMS, the effect of NLCs on the TMS permeability across Caco-2 cell monolayers was investigated. In our previous study, tilmicosin was proved to be a substrate of P-gp, a drug efflux transporter [35]. Herein, we found that the efflux rate of 10% TMS in Caco-2 cell monolayers was 2.29 (Table 2), far higher than the 1.5 regulated by the United States Food and Drug Administration [36], further demonstrating that TMS as the substrate of P-gp could be removed from intestinal epithelial cells and its oral absorption thereby decreased [25].…”
Section: Evaluation Of Tms Permeability Across Caco-2 Cell Monolayersmentioning
confidence: 99%
“…The borderline for the low/high permeability must be defined when evaluating permeability ( P app ) data from cell monolayer, and metoprolol is currently an acceptable and widely used marker for this purpose (Incecayir, Tsume, & Amidon, ; Zur et al, ), so metoprolol was used to be a reference standard for class in our research, and the classification results formed a good correlation with the absorption of drugs in chickens. LogP has been used for the permeability classification of canine BCS and pediatric BCS, and a LogP value greater than 1.72 as high permeability (Guimaraes et al, ; Papich, ), but the LogP only represents the lipophilic of drug molecules, and it ignores the enzymes and transporters inherent in human or animal organisms, thus, it is not surprising that predictions based only on LogP may frequently be in error, often because most drugs may be substrates for some transporter (Papich, ; Wu & Benet, ), such as some substrates (ciprofloxacin hydrochloride for P‐gp and BCRP; sulfadiazine for P‐gp) in our study (Zhang et al, ), which with a higher LogP value but a lower absorption in chicken. Moreover, we also discussed the role of pH on permeability class, and the result showed that pH has less influence on classification, except sulfamethoxazole, which was an acid drug (pKa 5.6), exhibits high class under pH 5.5 but low under pH 7.4, and it is well interpreted that acid drugs have higher permeability values at lower pH (Tolle‐Sander, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 1% glutamine and 1% penicillin under 37°C, and 5% CO 2 . MDCK-chAbcb1/Abcg2 cell line stably expressing chicken P-gp and BCRP was established in our laboratory (Zhang, Huang, Liu, Guo, & Wang, 2018). The cell lines were cultured as the above and supplemented with 1.0 μg/ml puromycin and 1 200 µg/ml neomycin.…”
Section: Cell Monolayer Culture and Integrity Verificationmentioning
confidence: 99%
“…Xenobiotics, including natural compounds (daidzein and berberine), commonly used drugs (rifampicin, clotrimazole, enrofloxacin, florfenicol, tilmicosin, sulfadiazine, ciprofloxacin, doxycycline, cefuroxime sodium, and ivermectin) and LPS, were used in the transfection assay. The concentrations of the above xenobiotics were selected according to the cytotoxicity assay results, where the concentrations were based on cell viabilities of no less than 90% compared with the control group [34]. The final concentrations of all of the xenobiotics were 30 µM, except ivermectin (10 µM) and LPS (50 µg/mL).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%